Size-related mineralogical and surface physicochemical properties of the mineral particles from the recent sediments of the Eastern Adriatic Sea. (June 2020) - Ivanić, Maja; Durn, Goran; Škapin, Srečo D.; Sondi, Ivan
Abstract: The mineral composition and surface physico-chemical properties, i.e., specific surface area (SSA), cation exchange capacity (CEC), and surface charge of recent sediments and their submicron mineral fractions from different sedimentological environments of the Eastern Adriatic were investigated. The influence of organic matter on these properties was also investigated. It was shown that illite and mixed-layered clay minerals (MLCM) were ubiquitous and showed no size-related preferences while the occurrence of smectites, chlorites, and kaolinites varied. The smectites content increased and the chlorites decreased slightly with decreasing particle size. The sediments from the carbonate-rich environment contained no smectites or chlorites and had the highest kaolinite content. For the first time, in the recent sediments of the Adriatic Sea the poorly- and the well-crystallised kaolinite (Kl and KlD ) were distinguished. While Kl predominates in the submicron-sized fraction, KlD occurred only in micron-sized fractions. Authigenic aragonite of submicron-sized was determined in a distinct environment of the semi-enclosed marine lake. The differences in mineral composition and particle size of sediments and their separated fractions were reflected in a wide range of the SSA and CEC values obtained. The highest values of SSA and CEC were determined in the phyllosilicates-rich submicron-sized fractions range, 109 m 2 g -1 and 87.4 cmol+ kg −1, respectively. The submicron-sized fraction from aragonite-rich marine lake showed the lowest values of SSA (56.4 m 2 g -1 ) and CEC (38.8 cmol+ kg −1 ), which are still unexpectedly high for carbonate-rich environments. The removal of organic matter resulted in a significant increase in SSA and CEC, up to 150% and 76%, respectively. Graphical abstract: Image 1 Highlights: Micron and submicron-sized fractions of recent Adriatic sediments were investigated. Mineralogical and surface properties of mineral particles are size related. Phyllosilicate-rich submicron-sized sediment fraction showed highest SSA and CEC. The removal of organic matter resulted in a significant increase in SSA and CEC. Prevalence of submicron-sized authigenic aragonite induced low SSA and CEC.